Role of STAT1 and Oxidative Stress in Gentamicin-Induced Hair Cell Death in Organ of Corti. Issue 9 (October 2016) - Jiang, Peng; Ray, Amrita; Rybak, Leonard P.; Brenner, Michael J.
Abstract : Rationale: Oxidative stress plays a critical role in gentamicin-induced hair cell death. Previous work has implicated the cytoplasmic transcription factor signal transducer and activator of transcription 1 (STAT1) as a potential mediator of drug-induced ototoxicity, but role in aminoglycosides is largely unknown. This study investigated aminoglycosides-induced cell death, exploring contributions of reactive oxygen species and STAT1 pathway in injury and protection. Methods: Neonatal murine organ of Corti explants from 2 to 3 day postnatal pups (n = 96) were treated with gentamicin at (4 μM, 50 μM) for 4 to 72 hours, with/without protectants. Effects on STAT1 pathway and gentamicin-induced hair cell death were measured with 50 μM Epigallocatechin gallate (EGCG, a STAT1 inhibitor) and all-trans retinoic acid (atRA, a STAT1 activator). Hair cell morphology was evaluated and hair cell loss was quantified with cytocochleograms. Mitochondrial membrane potential was assayed and superoxide generation and suppression was measured with dihydroethidium (DHE) staining. Results: Co-administration of 50 μM EGCG conferred protection from 4 μM gentamicin toxicity ( p < 0.001), whereas atRA potentiated gentamicin-induced hair cell death ( p < 0.001). On immunohistochemistry, STAT1 phosphorylation at theserine 727 (Ser 727 ) residues was increased at 72 hours with 4 μM gentamicin. With administration of 50 μM gentamicin, there was activation of STAT1 Tyr 701 at 4 hours and STAT1 Ser 727 at 16 hours. Gentamicin dissipated mitochondrial membrane potentials, and EGCG attenuated gentamicin-induced oxidative stress at 72 hours. Conclusion: EGCG protected outer hair cells from gentamicin toxicity in a cochlear explant model, with the underlying mechanism involving both reactive oxygen species (ROS) suppression and STAT1 inhibition. Abstract : Supplemental Digital Content is available in the text